Pemanfaatan Artificial Intelligence (AI) dalam Pembentukan Peraturan Perundang-undangan Serta Implikasinya Terhadap Etika dan Keamanan - Mardayanti, Imelda; Arfah, Yenni; Arseto, Dedy Dwi (STIE Bina Karya, 2024)
This research is about the use of artificial intelligence (AI) in the formation of laws and regulations and its implications for ethics and security. The method used in this research is a normative juridical legal research method. Normative research must use a statutory and regulatory approach. The data obtained is then collected through documentary study or literature study data collection techniques. Data (legal materials) obtained from library research were analyzed using qualitative methods. The results of Artificial Intelligence (AI) research are used to form legislation which is considered to be an effort to develop regulations and control the law enforcement system using technological devices. The existence of AI can be utilized by various sectors, including banking, trade, health, and the law enforcement sector. The definition relating to AI in the ITE Law is potentially unable to cover the evolution of AI. Law enforcement is influenced by several factors, in the field of technology, the factors that are important are facilities and infrastructure.